Optimization of Samapta Two-Wheel Patrols in Preventing Motor Vehicle Theft Criminal Actions to Realize Maintenance, Security, and Community Order in the Legal Area of Temanggung Polres - Bimantoro, Suryo (Advances in Police Science Research Journal, 2024)
The purpose of this research is that people feel safe and comfortable and conducive in the community environment. In writing this final project, the author uses concepts and theories as analytical tools such as optimization concepts, crime prevention concepts, two-wheeled patrol concepts, management theory, SWOT theory, and competence theory. The approach used in this study is a qualitative approach. Data collection techniques using observation techniques, interview techniques, and document studies. Data analysis techniques were carried out using data reduction techniques, data presentation, and verification. Based on the results of the study, it was shown that the implementation of patrol activities by the Temanggung Police’s two-wheeled Patrol Unit in preventing the crime of motor vehicle theft was still not optimal because public awareness was still low and several obstacles were found including the ability and education of personnel, limited number of personnel, and conditions inadequate facilities and infrastructure. Therefore, innovations are needed.